2019
DOI: 10.1002/ange.201809508
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of d‐Amino Acids in Minimalistic Peptide Substrates by an S‐Adenosyl‐l‐Methionine Radical Epimerase

Abstract: Post-translational modifying enzymes from the Sadenosyl-l-methionine (AdoMet) radical superfamily garner attention due to their ability to accomplish challenging biochemical reactions.A mong them, af amily of AdoMet radical epimerases catalyze irreversible l-t od-amino acid transformations of diverse residues,i ncluding 18 sites in the complex sponge-derived polytheonamide toxins.H erein, the in vitro activity of the model epimerase OspD is reported and its catalytic mechanism and substrate flexibility is inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…32 This peptide is consecutively post-translationally epimerized at isoleucine (I4) and valine (V13) residues by the S-adenosyl-L-methionine radical epimerase OspD to afford D-valine (v13) and D-allo-isoleucine (i4) residues. 33 We prepared the parent, all-L, peptide and those containing either only i4 or both i4 and v13 (E1−E3, Figure 4c) and recorded their blinking patterns as described before. Even in this very challenging peptide fingerprinting case, we could obtain an overall classification accuracy of 79% (Figure 4d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 This peptide is consecutively post-translationally epimerized at isoleucine (I4) and valine (V13) residues by the S-adenosyl-L-methionine radical epimerase OspD to afford D-valine (v13) and D-allo-isoleucine (i4) residues. 33 We prepared the parent, all-L, peptide and those containing either only i4 or both i4 and v13 (E1−E3, Figure 4c) and recorded their blinking patterns as described before. Even in this very challenging peptide fingerprinting case, we could obtain an overall classification accuracy of 79% (Figure 4d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pasteur Collection of Cyanobacteria (PCC) 6506) . This peptide is consecutively post-translationally epimerized at isoleucine (I4) and valine (V13) residues by the S -adenosyl- l -methionine radical epimerase OspD to afford d -valine (v13) and d - allo -isoleucine (i4) residues . We prepared the parent, all- l , peptide and those containing either only i4 or both i4 and v13 ( E1–E3 , Figure c) and recorded their blinking patterns as described before.…”
Section: Resultsmentioning
confidence: 99%
“…His 6 -tagged OspA precursor protein substrates were produced as previously described (Figure S5). 15 In an initial set of experiments, the ability of OspR to convert the Arg8 and Arg15 residues in the core sequence of OspA to the expected ornithine and urea products was monitored by two assays: Peptide products were detected by liquid chromatography-high resolution mass spectrometry (LC-HRMS) following proteolytic release of the OspA -5-16 core peptide fragment from His 6 -OspA (12.8 kDa) by digestion with glutamyl endoprotease (GluC). Urea was detected by a commercially available end-point spectrophotometric assay monitoring urea formation at 430 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Prior experimental results from full-cluster and OspR coexpressions in E. coli and in vitro analysis of OspD demonstrated that the OspA core is processed in an N- to C-terminal direction by all maturases in the pathway. Furthermore, the activity of OspM was dependent on the presence of d -amino acids, suggesting that epimerization at Ile4 occurs prior to formation of Cys2–Ser7 lanthionine .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation